The effect of postponement of first motherhood on permanent involuntary childlessness and total fertility rate in six European countries since the 1970s - te Velde, Egbert; Habbema, Dik; Leridon, Henri; Eijkemans, Marinus (Human reproduction (Oxford, England), 2012)
BACKGROUND: Postponement of childbearing since the 1970s has led to an increase in permanent involuntarily childlessness. We will address the magnitude of this trend, the effect of IVF/ICSI and the effect on total fertility rate (TFR an often used demographic measure for the level of fertility) in six EU countries. METHODS: Using a fertility micro-simulation model, we estimate the effect of postponement of first motherhood on permanent involuntary childlessness in six representative European countries since 1970/1985: Sweden, Austria, Czech Republic, The Netherlands, West Germany and Spain. To estimate the effect of IVF/ICSI on this trend, we use data on the results of all IVF/ICSI cycles performed in The Netherlands in 2003 and 2004. RESULTS: Permanent involuntary childlessness approximately doubled since 1970s and rose to ~4% in the Czech Republic and to ~7% in Spain with the other countries in between. If all couples entitled to have IVF/ICSI were to be treated, the effect of postponement would almost have been neutralized. However, only a limited proportion of eligible couple are being treated. Without postponement, TFRs would have been between 0.03 and 0.05 higher. CONCLUSIONS: The effect of postponement on permanent involuntary childlessness is considerable. So far IVF/ICSI only had a slight effect on this trend. The impact of postponement on TFRs is small compared with other demographic trends.
Keywords: Reproductive Behavior; Maternal Age; Czech Republic; Female; Humans; Infertility; Birth Rate; věk matky; lidé; Spain; Socioeconomic Factors; Švédsko; asistovaná reprodukce; ženské pohlaví; Španělsko; Fertility; reprodukční chování; infertilita; Reproductive Techniques, Assisted; Česká republika; Sweden; Nizozemsko; Netherlands; Rakousko; fertilita; socioekonomické faktory; Německo západní; dospělí; Adult; Germany, West; Austria; porodnost